HUBUNGAN ANTARA SELF CONTROL DENGAN INTENSITAS KEKERASAN PACARAN PADA REMAJA DI SUMATERA BARAT - Syahnur, Nofriadi; Ningsih, Yuninda Tria (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
This study aims to explore the relationship between self-control and the intensity of dating violence among teenagers in West Sumatra. The research utilizes a correlational method with a quantitative approach. Data collection involves accidental sampling with a sample size of 349 dating individuals. Data is gathered through questionnaires utilizing the Self-Control Scale (SCS) developed by Tangney, Baumeister, and Boone (2004), as well as the Conflict in Adolescent Relationships Inventory (CADRI) scale developed by Wolfe and Feiring (2000). Analysis of the correlation between the two variables yields a correlation coefficient value of .000 (p<0.05), indicating a significant relationship between self-control and dating violence.